Katekese Digital: Cara Gereja Menghadapi Tantangan Komunikasi Iman di Era Digital - Kristeno, Marianus Rago; Tarihoran, Emmeria (Vocat : Jurnal Pendidikan Katolik, 2024)
The XXI century is a century where technological advances are increasingly developing. Technological advances have penetrated almost all areas of human life. With advances in technology, social communication media have emerged that are integrated in practical devices and help a lot in various human jobs. The Church views this as an opportunity to convey teachings of the faith and catechesis. Digital catechesis is a form of catechesis that utilizes digital media, such as TikTok, Instagram, YouTube, Twitter, etc., which helps the Church to provide interesting, relevant, creative and innovative spiritual services. Through these digital media, the Church spreads the Gospel and provides teachings to the people. This article was written using a literature review method by collecting various writings, such as books, articles, journals, papers, etc. that are relevant to the problem discussed in this article. Digital catechesis is the Church's way of teaching the faith to the people and proclaiming Christ's teachings to many people. Through digital catechesis, people can communicate their faith without being limited by space and time. Digital catechesis is a forum for collaboration between the clergy and the laity, where the clergy act as teachers and guardians of the true teachings and traditions of the faith, while the laity, especially young people, become evangelizers through content posted on digital media.